Without Thinking Twice: (Some Forms of) Ignorance as Moral Signaling - Licon, Jimmy Alfonso (Journal of cognition and culture, 2026)
Ignorance of the costs and benefits of actions, like aiding someone in distress without thinking twice, is a reliable moral signal of altruism and trustworthiness - such actions, performed while ignorant, risk incurring costs with little or no benefit. Why care? First, this paper contributes to the literature applying signaling theory to moral issues. Second, it highlights some moral benefits of ignorance. And finally, it stresses how reliable self-signals increase the likelihood that those who are benevolent, in the present, will act comparably in the future - moral identity motivates future moral action, and reliable signals shape that identity.